DINAMIKA COPING STRESS WANITA DEWASA AWAL YANG MENGALAMI ENDOMETRIOSIS - Indah Ratnayu Adhy Ningsih (Universitas Katolik Widya Mandala Surabaya, 2020)
When a woman is a teenager, she will experience menstrual periods. Menstrual pain is normal for a woman. If the woman continues to experience more pain than usual, this is one of the symptoms of endometriosis. The pain that arises makes a person experience stress due to the disease itself. To deal with stress, it is necessary to carry out a resistance strategy, namely a stress coping strategy. The aim of the researchers was to determine the dynamics of stress coping in early adult women with endometriosis. This study uses an inductive qualitative approach with phenomenological methods. The informants in this study were individuals diagnosed with endometriosis. Data collection in this study was carried out through an interview process with two research informants. The results of this study indicate that when the two informants were diagnosed with endometriosis, the impact felt by the two informants was feeling stressed, anxious and afraid of the pain they experienced. To deal with the stress experienced by the two informants, they came up with coping strategies. In the form of focus coping problem, the two informants dealt with pain by taking medication, compressing the stomach with warm water, changing diet and lifestyle. In addition, emotional focus coping treatment by diverting to other things such as self-suggestions.